Induction of Mitochondria-Mediated apoptosis in Ca ski human cervical cncer cells triggered by mollic acid arabinoside isolated from Leea indica - Wong, Y.H.; Abdul Kadir, H. (Hindawi, 2012)
Leea indica is a medicinal plant traditionally used to treat cancer. Through bioassay-guided approach, we isolated mollic acid arabinoside (MAA), for the first time from Leea indica. Here, we present the apoptosis-inducing effect of MAA on Ca Ski cervical cancer cells. Based on DAPI staining, MAA-treated cells manifested nuclear shrinkage, condensation, and fragmentation. We further confirmed the fragmentation of DNA using TUNEL assay. During early apoptosis, MAA caused the perturbation of plasma membrane through externalization of PS, followed by the formation of apoptotic blebs. Prior to these events, MAA triggered rapid dissipation of the mitochondrial membrane potential. In the upstream, MAA increased the expression of Bax, decreased the expression of Bcl-2, and augmented the Bax/Bcl-2 ratio. These findings suggested that MAA induced mitochondrial-mediated apoptosis in Ca Ski cells and thus provide the scientific explanation for the traditional application of this herbal medicine in cancer treatment.